High sensitive Ln3+/Tm3+/Yb3+ (Ln3+ = Ho3+, Er3+) tri-doped Ba3Y4O9 upconverting optical thermometric materials based on diverse thermal response from non-thermally coupled energy levels. Issue 1 (January 2019) - Liu, Shuifu; Cui, Jun; Jia, Junjie; Fu, Junxiang; You, Weixiong; Zeng, Qingyun; Yang, Youming; Ye, Xinyu
Abstract: Upconversion (UC) optical thermometers using the fluorescence intensity ratio (FIR) technique arising from the thermally coupled energy levels (TCLs) are still suffering from low sensitivity owing to the restriction of small energy gap. In the present study, a strategy to strive for superior temperature sensitivity and signal discriminability is employed with the help of non-thermally coupled energy levels (NTCLs). A novel tri-doped Ba3 Y4 O9 : Ho 3+ /Tm 3+ /Yb 3+ phosphor with rhombohedral symmetry was successfully prepared via a solid-state reaction method, and the temperature sensing performance was evaluated by analyzing temperature-dependent upconversion emission spectra. The emission intensities of both Ho 3+ and Tm 3+ activators can be almost completely restored to their original values when the temperature of the sample is cooled to room temperature. The temperature-dependent FIR between NTCLs can be fitted well by a derived three-term equation with the correlation coefficient above 99.6%, and the FIR of NTCLs exhibits high temperature sensitivity over a wide temperature range owing to the different temperature responses of the NTCLs. The maximum absolute sensitivity S A and relative sensitivity S R values reaches as high as 0.0552 K −1 and 1.49% K −1, respectively, which are much higher than those of the previously reported bulk UC optical temperature sensing materials. Moreover, the emission bands of NTCLs are well separated, which endows the material a good signal discriminability for temperature detection. Excellent temperature sensing performance is also demonstrated in Er 3+ /Tm 3+ /Yb 3+ tri-doped Ba3 Y4 O9, evidencing the validity of this strategy. These results indicate that the present UC materials can be potential candidates for optical temperature sensors, and the present strategy will provide a thought for developing other innovative UC temperature sensing materials.